A utilização de Cenários para Investigação no estudo de frações - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This study presents research conducted in a sixth-grade class of a public school in Bagé/RS, focusing on the application of a set of activities on the topic of fractions. It incorporates the concepts of Scenarios for Investigation developed by Ole Skovsmose within the field of Critical Mathematics Education. The objectives of this work were to assess the feasibility and effectiveness of the Scenarios for Investigation methodology for teaching fractions in a public school and to understand if students felt more motivated when using this methodology. To achieve these objectives, activities were planned based on Skovsmose's framework (2014), which explores the different learning environments of the Scenarios for Investigation methodology. One of the proposed activities involved the use of fraction disks as instructional materials to aid in the representation of fractions. Additionally, a research project was conducted among the students to explore their individual preferences, and the obtained data were used for students to represent their preferences. Among the most significant results of the study, it was found that students approved the use of the methodology but emphasized the importance of expository moments as well.
Keywords: Cenários para Investigação; Fração; Educação Matemática Crítica; Scenarios for Investigation; Fraction; Critical Mathematics Education; CNPQ::CIENCIAS EXATAS E DA TERRA